Penyelesaian Perkara Pencurian sebagai Tindak Pidana Ringan Pasca Peraturan Mahkamah Agung Nomor 2 Tahun 2012 - Gede Mahadi Waisnawa Hanata Putra; I Nyoman Putu Budiartha; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
Indonesian Criminal Law is currently a legacy from the Dutch East Indies Government which has been adapted and passed by Law No. 16 of 1946 to be implemented nationally. The purpose of this research is to describe the regulation of theft of minor crimes in the Criminal Code before the Supreme Court Regulation Number 2 of 2012 and to describe the juridical consequences of Supreme Court Regulation No.2 of 2012 on theft as a minor criminal act in the Criminal Code. This research uses normative legal research methods. The results show that according to Article 206 of the Criminal Procedure Code, procedures for granting authority to investigate and review cases are carried out by the investigator himself and should not be disturbed by the prosecutor. This Perpres adjusts articles 364, 373, 379, 384, 407 and article 482 of the Criminal Code to Rp. 2,500,000.00. Therefore, fulfill this element of the requirement and enter a case where the value of the commodity does not exceed Rp. 2,500,000.00. Therefore, the case is examined by expedited procedure, which is tried by a judge, and the assignment and review of the case is carried out by the investigator himself without the interference of the prosecutor.